An Analysis of the Inclusion of Different Genders in BLP Beauty’s Brand Image - Johan, Hanni Shabrina; Andayani, Nadia Marita (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
In recent years, beauty brands have begun to incorporate different genders into their brand image. This phenomenon emerged as a big change for the beauty industry because beauty products at that time only targeted women. In the past, using cosmetics was generally only reserved for women. The use of cosmetics for men is considered inappropriate and strange. BLP Beauty is an Indonesian beauty brand that prioritizes inclusivity towards all genders. BLP Beauty features different genders on their social media ads to promote their inclusivity, which they specifically use inclusive marketing strategies to achieve their goals. This research discusses the implementation of an Inclusive Marketing Strategy through the Creative Elements model applied by BLP Beauty in their social media advertisements on Instagram. Through content analysis from a qualitative approach, the findings show that BLP Beauty uses these models to carry out their social media advertising on Instagram. Social media advertising content on the official BLP Beauty Instagram account proves the use of Creative Elements in implementing an Inclusive Marketing Strategy. To encourage more opportunities, researchers need to analyze BLP Beauty's other social media platforms.